TRUST AND CUSTOMER SATISFACTION BASED SERVQUAL IN SOCIAL SECURITY AWARENESS MARKETING PROGRAM - Yumi, Raudah Rakhmah; Marsasi, Endy Gunanto (Institut Teknologi dan Bisnis Asia Malang, 2024)
Researchers examined a company in the social insurance industry with a socialization marketing program for companies and non-formal workers that aims to attract workers to become company customers. This research was conducted to assist and propose a marketing program that can be applied to companies, namely the Social Security Awareness program. The method of analysis of this research is qualitative, with direct observation, in-depth interviews, collection of documents, and secondary information from the company. Research is carried out in companies through the field of marketing. Based on the research conducted, this program can increase company membership by making employees or potential customers aware of the importance of using the company's products. This research produces a program proposal using the SERVQUAL theory through the concepts of trust and customer satisfaction, which are expected to be implemented in the company's system to support the implementation of the Social Security Awareness marketing program.